2023
DOI: 10.1111/birt.12713
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth among Pacific Islanders in the United States and the US‐affiliated Pacific Islands: A systematic review and meta‐analysis

Abstract: Objective To better understand the epidemiology of preterm birth among Pacific Islanders in the United States and the US‐Affiliated Pacific Islands. Methods Systematic searches of MEDLINE, Embase, CINAHL, PsycINFO, two nonindexed regional journals, and gray literature were conducted and finalized in September 2021. Observational studies published since January 2010 that documented preterm birth outcomes among Pacific Islanders in the United States and the US‐Affiliated Pacific Islands were eligible for inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 72 publications
0
4
1
Order By: Relevance
“…Thus, to ensure that undercounted people receive better benefit from research and associated health care interventions, innovative ways to reclassify individuals who select the other racial and ethnic category should be explored, such as offering more detailed self-identification options on surveys or applying machine-learning techniques to evaluate write-in responses to the other category. Native Hawaiian or Other Pacific Islander populations are another group underrepresented in perinatal research and are often aggregated with Asian people, which may mask their unique outcomes given the heterogeneity within both Native Hawaiian or Other Pacific Islander and Asian subgroups . Native Hawaiian or Other Pacific Islander birth outcomes are important to study as they are one of the fastest-growing minoritized groups in the US, with substantial intragroup variation in perinatal outcomes …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, to ensure that undercounted people receive better benefit from research and associated health care interventions, innovative ways to reclassify individuals who select the other racial and ethnic category should be explored, such as offering more detailed self-identification options on surveys or applying machine-learning techniques to evaluate write-in responses to the other category. Native Hawaiian or Other Pacific Islander populations are another group underrepresented in perinatal research and are often aggregated with Asian people, which may mask their unique outcomes given the heterogeneity within both Native Hawaiian or Other Pacific Islander and Asian subgroups . Native Hawaiian or Other Pacific Islander birth outcomes are important to study as they are one of the fastest-growing minoritized groups in the US, with substantial intragroup variation in perinatal outcomes …”
Section: Discussioncontrasting
confidence: 99%
“…Native Hawaiian or Other Pacific Islander populations are another group underrepresented in perinatal research 38 and are often aggregated with Asian people, which may mask their unique outcomes given the heterogeneity within both Native Hawaiian or Other Pacific Islander and Asian subgroups. 39,40 Native Hawaiian or Other Pacific Islander birth outcomes are important to study as they are one of the fastest-growing minoritized groups in the US, 41 with substantial intragroup variation in perinatal outcomes. 17 Second, we found that non-US-born Native Hawaiian or Other Pacific Islander birthing people did not experience the immigrant paradox or the expected non-US-born advantage in preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…We then used Cox proportional hazard regression models to examine associations between characteristics and PTB, with the time variable of GA at birth. Covariates in the univariable models were selected based on previous literature [3,8,23],…”
Section: Study Importancementioning
confidence: 99%
“…Among US singletons born without congenital anomalies, PTB prevalence increased from 7.6% to 8.1% [2] between 2014 and 2018, with Black women having the highest (11.2%) and White women having the lowest prevalence (7.2%) [2]. Pacific Islander women in the United States (PTB prevalence: 11.2%) [3] also have a higher risk of PTB compared with White women [3], but our understanding of risk factors underlying this disparity is limited because Pacific Islander individuals have been traditionally aggregated with Asian American individuals, whose demographic characteristics and biomedical risk profiles are quite dissimilar [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation